Incidence and characteristic of psoriasis patients at Sanjiwani Gianyar Regional Hospital 2018-2019 - Annisa Alviariza; Sayu Widyawati (Bali Dermatology Venereology and Aesthetic Journal, 2020)
Introduction: Psoriasis is a chronic inflammatory skin disease characterized by firmly demarcated red plaque covered by a thick squama due to impaired proliferation and differentiation of the epidermis. Diagnosis of psoriasis is based on history taking and clinical features. Treatment is determined based on the patient's clinical characteristics and the severity of the disease. This retrospective study aims to determine the incidence, characteristics, and treatment options of psoriasis patients in the Dermatology and Venereology Polyclinic of Sanjiwani Gianyar Regional Hospital in 2018-2019. Methods: A retrospective study of psoriasis patients at Sanjiwani Gianyar Regional Hospital in 2018-2019. Data collected from medical records includes sociodemographic data, clinical data, and patient treatment history. Results: Within two years, there were 53 cases of psoriasis. The dominance of psoriasis cases was found in men with a ratio of women and men 1:2.31. Of total 53 patients, 37 were male (69.81%)and 16 female patients (30.19%). The most common type was psoriasis vulgaris (73.58%). The most age group was 31-45 years. The most commonly given regimen of therapy was topical corticosteroids plus oral antihistamines (45.28%). The most widely given systemic therapy was methotrexate. Accompanying skin infections were found in 6 cases of psoriasis (11.32%). Conclusion: Based on the results of the study, there were 53 new cases of psoriasis in 2018-2019, psoriasis vulgaris was the most common, the most age group was 31-45 years old, topical corticosteroids with antihistamines were still the main treatment options for psoriasis patients in Sanjiwani Gianyar Regional Hospital.